2013
DOI: 10.7852/ijie.2013.27.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Bombyx mori Decapentaplegic gene for bone differentiation in a mammalian cell

Abstract: Bone morphogenetic proteins (BMPs) belong to the transforming growth factor (TGF-b) superfamily and are involved in osteoblastic differentiation. The largest TGF-b superfamily subgroup shares genetic homology with human BMPs (hBMPs) and silkworm decapentaplegic (dpp). In addition, hBMPs are functionally interchangeable with Drosophila dpp . Bombyx mori dpp may induce bone formation in mammalian cells. To test this hypothesis, we synthesized the 1,285-base pairs cDNA of full-length B. mori dpp using total RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…mori , is highly conserved, and has been found in human, cow, mouse, chicken and fruit fly (Park et al . ). In particular, B .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…mori , is highly conserved, and has been found in human, cow, mouse, chicken and fruit fly (Park et al . ). In particular, B .…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, it was able to convert the differentiation pathway of these stem cells to form osteoblast lineage cells (Park et al . ). Another study showed that silkworm pupa significantly contributes to the prevention or treatment of bone loss induced by ovariectomization in rats (Ryu et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations